To get to the end of the trail it would take 2 hours because the walking back hours would be double the walking out rate, but it would still have to equal 6 hours. So walking out would be 2 hours and walking back would be 4 hours which makes the trail 8 miles long.
To solve such questions we need to know more about expression.
<h2 /><h2>Expression
</h2>
In mathematics, an expression is defined as a set of numbers, variables, and mathematical operations that are formed according to rules which are dependent on the context.
<h2 /><h2 /><h2>Given to us,</h2>
![2\sqrt[4]{16x}-2\sqrt[4]{2y}+3\sqrt[4]{81x}-4\sqrt[4]{32y}+5\sqrt[4]{x}-4\sqrt[4]{32y}+5\sqrt[4]{x}-16\sqrt[4]{2y}+13\sqrt[4]{4}-10\sqrt[4]{2y}+35\sqrt[4]{x}-18\sqrt[4]{2y}](https://tex.z-dn.net/?f=2%5Csqrt%5B4%5D%7B16x%7D-2%5Csqrt%5B4%5D%7B2y%7D%2B3%5Csqrt%5B4%5D%7B81x%7D-4%5Csqrt%5B4%5D%7B32y%7D%2B5%5Csqrt%5B4%5D%7Bx%7D-4%5Csqrt%5B4%5D%7B32y%7D%2B5%5Csqrt%5B4%5D%7Bx%7D-16%5Csqrt%5B4%5D%7B2y%7D%2B13%5Csqrt%5B4%5D%7B4%7D-10%5Csqrt%5B4%5D%7B2y%7D%2B35%5Csqrt%5B4%5D%7Bx%7D-18%5Csqrt%5B4%5D%7B2y%7D)
rearranging we get,
![=2\sqrt[4]{16x}+3\sqrt[4]{81x}+5\sqrt[4]{x}+5\sqrt[4]{x}+13\sqrt[4]{4}+35\sqrt[4]{x}-2\sqrt[4]{2y}-4\sqrt[4]{32y}-4\sqrt[4]{32y}-16\sqrt[4]{2y}-10\sqrt[4]{2y}-18\sqrt[4]{2y}](https://tex.z-dn.net/?f=%3D2%5Csqrt%5B4%5D%7B16x%7D%2B3%5Csqrt%5B4%5D%7B81x%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B13%5Csqrt%5B4%5D%7B4%7D%2B35%5Csqrt%5B4%5D%7Bx%7D-2%5Csqrt%5B4%5D%7B2y%7D-4%5Csqrt%5B4%5D%7B32y%7D-4%5Csqrt%5B4%5D%7B32y%7D-16%5Csqrt%5B4%5D%7B2y%7D-10%5Csqrt%5B4%5D%7B2y%7D-18%5Csqrt%5B4%5D%7B2y%7D)
we know that,
![\sqrt[4]{81}=3\\\sqrt[4]{16}=2\\\sqrt[4]{32}=2\sqrt[4]{2}\\](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B81%7D%3D3%5C%5C%5Csqrt%5B4%5D%7B16%7D%3D2%5C%5C%5Csqrt%5B4%5D%7B32%7D%3D2%5Csqrt%5B4%5D%7B2%7D%5C%5C)
therefore,
![=4\sqrt[4]{x}+9\sqrt[4]{x}+5\sqrt[4]{x}+5\sqrt[4]{x}+13\sqrt[4]{x}+35\sqrt[4]{x}-2\sqrt[4]{2y}-8\sqrt[4]{2y}-8\sqrt[4]{2y}-16\sqrt[4]{2y}-10\sqrt[4]{2y}-18\sqrt[4]{2y}](https://tex.z-dn.net/?f=%3D4%5Csqrt%5B4%5D%7Bx%7D%2B9%5Csqrt%5B4%5D%7Bx%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B13%5Csqrt%5B4%5D%7Bx%7D%2B35%5Csqrt%5B4%5D%7Bx%7D-2%5Csqrt%5B4%5D%7B2y%7D-8%5Csqrt%5B4%5D%7B2y%7D-8%5Csqrt%5B4%5D%7B2y%7D-16%5Csqrt%5B4%5D%7B2y%7D-10%5Csqrt%5B4%5D%7B2y%7D-18%5Csqrt%5B4%5D%7B2y%7D)
taking
and
as common
=![[(\sqrt[4]{x})(4+9+5+5+13+35)]-[(2+8+8+16+10+18)(\sqrt[4]{2y})]](https://tex.z-dn.net/?f=%5B%28%5Csqrt%5B4%5D%7Bx%7D%29%284%2B9%2B5%2B5%2B13%2B35%29%5D-%5B%282%2B8%2B8%2B16%2B10%2B18%29%28%5Csqrt%5B4%5D%7B2y%7D%29%5D)
Further simplifying
![=71\sqrt[4]{x}-62\sqrt[4]{2y}](https://tex.z-dn.net/?f=%3D71%5Csqrt%5B4%5D%7Bx%7D-62%5Csqrt%5B4%5D%7B2y%7D)
Learn more about the expression:
brainly.com/question/13947055?referrer=searchResults
The Pythagorean Theorum formula is a(squared) + b(squared)= c(squared). If you plug in the numbers, the equation is 39(squared) + 80(squared)= c(squared). That simplifies to 1521+6400=c(squared). Adding results in 7921=c(squared). Finally, when you take the square root of both sides, you are left with 89=c (aka the hypotenuse)
Let x is Jiri's age
2x is Pamela's age
x + 2x = 33
3x =33
x = 33/3
x =11
Answer: Jiri's age is 11
Answer:
hi
Step-by-step explanation: